Analisis Kemampuan Representasi Peserta Didik Pada Praktikum Kimia Materi Asam Basa Kelas Xi Sains SMAN 2 Mataram - Nurul Fitriani; Muntari Muntari; Dodiy Firmansyah (Chemistry Education Practice, 2025)
This study aims to analyze the chemical representation abilities of students at the macroscopic, submicroscopic, and symbolic levels in acid-base material practicums in class XI Science of SMAN 2 Mataram. The type of research is descriptive quantitative. The study population was 288 students of class XI SMAN 2 Mataram. The research sample was selected using purposive sampling technique obtained by class XI Science 7 students totaling 36 students and class XI Science 8 students totaling 36 students. Data collection techniques used interview, observation, documentation, and test instruments. Data analysis used N-gain percentage. The results showed that students' initial chemical representation abilities were relatively low, with an average pretest of 34.50% (macroscopic), 31.00% (submicroscopic), and 35.00% (symbolic). After the lab-based learning, posttest results showed significant improvements at all levels of representation, namely 85.25% (macroscopic), 78.25% (submicroscopic), and 76.50% (symbolic). The average total improvement increased from 33.50% to 79.99%, and is considered good. These results indicate that the chemistry lab is effective in improving students' representational skills on acid-base material.